Mobility tracking using Radio Frequency Identification (RFID) - Suryani Sortin (2014)
Radio Frequency Identification or generally known as RFID devices has became increasingly popular from time to time. It is comprehensively used for items inventory management and tracking. Its automated data-capture and intelligent technology is more or less convenient for wireless and contactless applications.